2011
DOI: 10.3109/0886022x.2011.589941
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10and its Relation with Oxidant and Antioxidant System Markers in Patients with End-Stage Renal Disease

Abstract: Rationale and objectives: Oxidative stress is increased in chronic kidney disease (CKD) patients and end-stage renal disease (ESRD) patients undergoing dialysis treatment. Coenzyme Q 10 (CoQ 10 ) is a ubiquitous and strong antioxidant. Role of CoQ 10 is not fully evaluated in renal patients. We aimed to investigate the relationship of CoQ 10 with oxidant and antioxidant system markers in patients with renal disease. Material and methods: Forty patients with CKD (stages 3-5) who were managed conservatively with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This effect on not healthy population may attribute to the highest levels of inflammatory markers in patient than in healthy people. In agreeing with Lee et al study, Gokbel et al shows coenzyme Q10 (100 mg/day) in healthy population did not affect the inflammatory markers ( 19 ). The above mentioned dose seems not to be sufficient to reduce inflammatory markers which were not elevated among healthy people.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This effect on not healthy population may attribute to the highest levels of inflammatory markers in patient than in healthy people. In agreeing with Lee et al study, Gokbel et al shows coenzyme Q10 (100 mg/day) in healthy population did not affect the inflammatory markers ( 19 ). The above mentioned dose seems not to be sufficient to reduce inflammatory markers which were not elevated among healthy people.…”
Section: Discussionsupporting
confidence: 85%
“…In addition few recent studies look into the effect of coenzyme Q10 on inflammation and oxidative markers in CVD patients ( 16 - 18 ). Additionally, the possible relationship between coenzyme Q10 and oxidative stress markers in CKD patients was not been studies completely ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gokbel et al reported that serum levels of CoQ10 were lower in ESRD patients when compared with controls. 20 In an HD study population, Triolo et al also demonstrated abnormally low CoQ10 levels in 62% of patients. 21 They proposed that reduced CoQ10 levels may contribute to the defective serum antioxidant activity and the increased peroxidative damage in uremic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Gokbel et al. reported that serum levels of CoQ10 were lower in ESRD patients when compared with controls . In an HD study population, Triolo et al.…”
Section: Discussionmentioning
confidence: 96%
“…One observational study, comparing dialysis patients to healthy controls, found an association between lower co-enzyme blood levels and higher oxidative stress in dialysis patients (Mehmetoglu et al2012). This has not been a consistent finding and larger, higher powered studies are needed before this relationship can be accepted (Gokbel et al2011; Lippa et al1994). Another small study followed 36 HD patients for 6 months and showed that co-enzyme Q10 administration was partially effective for suppressing the oxidative stress in HD patients (Sakata et al2008).…”
Section: Quinones In Renal Diseasementioning
confidence: 99%